Choosing Treatment for Dogs With Generalised Demodicosis – Isoxazolines or Imidacloprid and Moxidectin? - Sarah Long (Veterinary Evidence, 2019)
PICO question In dogs with generalised demodicosis, are isoxazolines as effective as a combined formulation of imidacloprid and moxidectin at reducing mite count and the severity of associated clinical signs? Clinical bottom line Five single-blinded, randomised, positive control trials, most under laboratory conditions, directly compared the use of isoxazolines against moxidectin/imidacloprid to treat canine generalised demodicosis. All of them showed comparable efficacy of isoxazolines. Three different isoxazolines were studied with two routes of administration (oral and topical) and four different dosing frequencies of moxidectin/imidacloprid. This made the papers more challenging to compare however, the evidence provided is sufficient to support their use. All of these trials were sponsored by the manufacturers of their respective isoxazoline products which may bias the study design and reporting of results. It is worth noting that sarolaner (Simparica™, Zoetis UK) was licensed in the UK for the treatment of canine demodicosis in January 2018 and that in the UK the Cascade should be followed when prescribing treatments. The licensed use of isoxazolines in other countries is beyond the scope of this article and the reader is urged to check local regulatory body advice before prescribing the below medications.